Investigasi Teoretis Interaksi Nonkovalen antara β-Siklodekstrin dan Hidroksiklorokuin - Atthar Luqman Ivansyah (LPPM, Institut Teknologi Sepuluh Nopember, 2020)
There was an outbreak with symptoms similar to SARS caused by the SARS-CoV-2 virus in the People's Republic of China at the end of 2019. The rapid spread of the virus, even in Indonesia, led to a pandemic status being given by the WHO. The use of current medications before a vaccine is identified and ready for help is one alternative to reducing COVID-19 patients. As a candidate for anti-COVID-19 drugs, Hydroxychloroquine has been extensively studied and has now reached the clinical trial stage. Hydroxychloroquine's solubility in water, however, is so limited that it affects its low human body bioavailability. The development of a stable inclusion complex with β-cyclodextrin is one way to increase Hydroxychloroquine's solubility in water. This research investigated the interaction between β-cyclodextrin and Hydroxychloroquine through molecular docking analysis and a semiempirical quantum process. The results of the semiempirical quantum method and the study of molecular docking suggest that β-cyclodextrin and Hydroxychloroquine are a stable inclusion complex. Hydroxychloroquine's solubility in aqueous solution can also be increased by forming an inclusion complex with β-cyclodextrin.